2007
DOI: 10.1063/1.2784290
|View full text |Cite
|
Sign up to set email alerts
|

Single-mode laser action in quantum cascade lasers with spiral-shaped chaotic resonators

Abstract: The authors have fabricated and characterized quantum cascade lasers with spiral-shaped microresonators. The lasers operate in pulsed mode at room temperature with peak optical power greater than 20mW and in continuous wave at temperatures up to 125K. They exhibit single-mode emission in both pulsed mode and continuous wave operation, with a 30dB side-mode suppression ratio at injection currents well above threshold. Subthreshold spectral measurements indicate that the spiral cavities support whispering-galler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 11 publications
5
28
1
Order By: Relevance
“…Experimentally emission in approximately single direction was obtained by pumping optically or electrically only the edge of the cavity (Chern et al, 2003;Kneissl et al, 2004). Later studies showed that uniform pumping of the entire cavity does not produce directional output (Audet et al, 2007;. Further analysis revealed that pairs of CW and CCW modes do not exist in the spiral (Wiersig, 2008;.…”
Section: A Spiral-shaped Cavitymentioning
confidence: 99%
“…Experimentally emission in approximately single direction was obtained by pumping optically or electrically only the edge of the cavity (Chern et al, 2003;Kneissl et al, 2004). Later studies showed that uniform pumping of the entire cavity does not produce directional output (Audet et al, 2007;. Further analysis revealed that pairs of CW and CCW modes do not exist in the spiral (Wiersig, 2008;.…”
Section: A Spiral-shaped Cavitymentioning
confidence: 99%
“…One promising route to achieve this was the modification of the original circular boundary that, due to the inherent rotational symmetry, yields a uniform far field. Spiral-shaped microcavity laser [3] were one of the first geometries successfully tested in many experiments [4][5][6][7][8], and conditions for unidirectional light emission from spiral-shaped microcavities were studied in detail [9][10][11]. A triangular shape has been proposed especially for small lasers [12,13].…”
mentioning
confidence: 99%
“…Among these, electrically pumped semiconductor microcavity lasers such as stadiumshaped lasers, 5 bow-tie lasers, 6 and spiral-shaped lasers [7][8][9] are of special interests for potential applications and as tool to study ray and wave chaos. Up to now, however, very few studies of microcavities in both experiment 10 and theory 11,12 have shown promise of achieving directional emission while having high quality-factor ͑Q-factor͒ modes in the cavity.…”
mentioning
confidence: 99%